ANALISIS TINDAK TUTUR ILOKUSI DAN LOKUSI DALAM INTERAKSI PENJUAL DAN PEMBELI DI PASAR TRADISIONAL PATTALLASSANG - Rini Sukarni; A. Rahman Rahim; Arifuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the forms of illocutionary and locutionary speech acts in the interaction between sellers and buyers at the Pattallassang Market, Takalar Regency. A qualitative descriptive approach was employed. Data were collected through direct observation, non-participant observation, and recording of conversations during market activities. The results revealed 24 illocutionary speech acts classified into assertive, directive, commissive, expressive, and declarative categories. Additionally, 14 locutionary acts were identified, including imperative, interrogative, and declarative forms. The findings indicate that various types of speech acts play a vital role in establishing effective communication, fostering interpersonal relationships, and achieving negotiation agreements. This study suggests that understanding speech acts enhances communication quality in traditional market interactions and reduces misunderstandings.